The Nature, Methods and Functions of the Agricultural Management System in the Context of Economic Liberalization - Xasanov Ilyosbek Xursanbekovich (Research Parks Publishers, 2022)
In this article, the development of scientifically based and practical proposals and recommendations on increasing the efficiency of the agricultural management system in the conditions of economic liberalization is widely covered.